Chayamansa (Cnidoscolus aconitifolius) Growth of Twig from Branch Cutting based on Different Soils - DONSAVANH, Beun; BOUAPHAKEO, Pazeun; PHONCHALEUN, Sengkham; PHETLUMPHANH, Bounxian; CHANTHAKHOUN5, Vongpasith; SINGPA, Bounlum (Souphanouvong University Journal Multidisciplinary Research and Development, 2019)
The experimental propagation of Chayamansa by branch cutting is to study for branch growing based on different soils. This study aimed to identify the branch growth under different factors (soils), and to investigate those factors affect to branch cutting growth. The experiment applied the randomized completed block design (RCBD) system, which was managed into four groups of soil to a hundred branches per block on whole treatment. This experiment was uncontrollable of air condition and was divided factors into four groups and six sub-treatments for conducting of branch cutting. As a result, this study found that the soil groups of loamy mixed with chicken manure and soil, can stimulate the twig of branch growing faster than other groups while comparing the controlled soils and others. Moreover, the study investigated factors and treatments for significant in statistic at P-value<0.05, and this study attempted to identify the factors affect to twig growth, it found that the